Desenho institucional, participação social e percepção ambiental na gestão do Parque Nacional de Sete Cidades – Piauí – Brasil - Luz, Maria Ivaneide (2021)
Protected areas currently represent the most important global strategy for mitigating environmental problems. In this context, the Sete Cidades National Park (PNSC), located in the municipalities of Piracuruca and Brasileira - Piauí, has, in addition to its scenic beauty, rich biodiversity. The main objective of this research was to analyze the institutional design and the process of social participation in the management of the PNSC, based on: investigation of the degrees of institutionalization, participation and effectiveness, representativeness and communication of its Advisory Council; elaboration of a measurement index of the studied parameters; identification of the socio-cultural profile of the residents surrounding the park; description of the environmental perception of residents of communities surrounding the Conservation Unit (UC) regarding the valuation and the feeling of belonging to this conservation space. The methodology used the qualitative and quantitative approach through documentary research and field study. The documentary research took place through the consultation of administrative documents, books of minutes of meetings of the Advisory Council and current legislation, available at the park's headquarters office and on the website of ICMBIO (Chico Mendes Institute for Biodiversity Conservation). The field study was carried out by conducting 04 semi-structured interviews with the members of the PNSC Advisory Council and 49 questionnaires applied to residents of eight communities surrounding the park: Água da Abelha, Alto Bonito, Cachoeira, Capote, Extrema, Mata Fria, Morada Nova and Palmeira da Emília. The treatment of the data obtained used Content Analysis and Basic Statistics. The results show that the PNSC Advisory Council has an institutionalization based on current legislation, however needing a deeper discussion about its participatory and representative character, as well as its communication instruments. The study on the environmental perception of the residents of the park's surroundings pointed to a distance and a lack of identification of this population with the protected area. This reality requires an intensification of Environmental Education actions with the communities studied, addressing a recovery of the history, importance, benefits and conservation of the UC.